International Clinical Protocol on Vestibular Disorders (Dizziness). - Trinus, Kostiantyn; Claussen, Claus-Frenz (International Tinnitus Journal, 2017)
26-28 May at 43 Congress of Neurootological and Equilibriometric Society (Budapest, Hungary) International Clinical Protocol on Vestibular Disorders (Dizziness) being discussed and accepted as Consensus Document. Cochrane reports estimates that dizziness has prevalence of 22.9% in the last 12 months and an incidence of 3.1%. Only 1.8% of adults consulted a physician in the last 12 months. Cochrane reviews suggest that the evidence base for dizziness evaluation is weak, thus necessitates the creation of evidence-based document. Protocol is based at the new concept of vestibular system, which involves the vestibular peripheral sensors, space orientation tetrad, vestibular presentations in the brain cortex and vestibular effectory projections in the brain. Labyrinth consists of sensors, for which six modalities are adequate: 1. acceleration, 2. gravitation, 3. low frequency whole-body vibration, 4. Infrasound, 5. magnetic impulse, 6. metabolic changes. Vestibular system from rhomboid fosse gets the inputs from visual, acoustic, somatosensory organs, integrating them and forming space perception and orientation. Interaction with space is realized through sensory, motor, vegetative and limbic projections. So, vestibular disturbances may manifest as paropsia, tinnitus, numbness. Vestibular evoked potentials (not VEMP) and craniocorpography have highest sensitivity (90% and more). As vestibular dysfunction has recurrent character patients need monitoring.